OPTIMASI LAJU PRODUKSI DENGAN CARA DESAIN ULANG PROGRESSIVE CAVITY PUMP (PCP) PADA SUMUR “X” LAPANGAN “Y” - Prastio, Eko; Rizky Agusman, Abdullah (Jurnal Jaring SainTek, 2021)
Progressive Cavity Pump (PCP) has beenapplaid as artificial lift at X well that is ownedby PT Pertamina EP Asset 1 Field Jambi. Fromthe early calculation of current production gets17,16 bfpd that has not reached the target of48,57 bfpd. This indicates that PCP must beredesign. Before redisgn we used ProductivityIndex (PI) to make an Inflow PerformanceRelationship (IPR) curve that shows the oil isstill suitable production or not. We redisgn PCPusing R & M Energy Systems calculationmethods as the provider and found that theoptimal for revolution per minute (RPM), horsepower (HP), torque values and the drive headtype are 101,5 RPM, 2,7 HP, 15 ft-lbs and therehave to be a change in drive head type AA4. Toget results optimal production.